Unraveling Factors Influencing Local Willingness to Participate in Sustainable Komodo Conservation and Protected Area Tourism - Sianipar, Imelda Masni Juniaty; Lee, Chun-Hung; Wang, Hurng-Jyuhn; Kim, Doo-Chul; Suryawan, I Wayan Koko (Forestry Faculty, Universitas Hasanuddin, 2024)
Komodo National Park is at the forefront of balancing environmental conservation with the challenges and opportunities of sustainable tourism. This research delves into the attitudes and engagement levels of the local communities within Komodo's distinctive ecological context, aiming to unravel the factors that drive or hinder their involvement in sustainable tourism and conservation activities. Through Exploratory Factor Analysis, we distilled key influences on community engagement, followed by a K-Mean Cluster Analysis to segment the community by their involvement levels. Logistic Regression was then employed to explore the likelihood of continued participation in these initiatives. The analysis identified three primary factors affecting community participation: the degree of involvement in sustainable tourism activities, the extent of community and environmental involvement, and the level of awareness regarding tourism development policies. The Cluster Analysis illuminated diverse engagement patterns across demographic lines, revealing how differences in settlement type, income levels, marital status, gender, and age contribute to varied participation rates. Interestingly, the logistic regression pointed to a paradox where higher engagement in sustainable tourism correlates with a lower probability of future participation, hinting at possible sustainability fatigue among highly active community members. These intricate dynamics of community engagement in sustainable tourism within Komodo National Park, highlight the importance of tailored, demographic-specific approaches to foster inclusive participation in conservation efforts. The insights gained underscore the complexity of promoting sustainable tourism in sensitive ecological areas and offer critical recommendations for policymakers and conservation stakeholders aiming to enhance sustainable development in Komodo and similar settings globally.